Good Islamic Boarding School Foundation Management as Risk Mitigation for Organizational Performance Management & GCG - Saleh, Mulyana; Indupurnahayu, Indupurnahayu; Beik, Irfan Syauqi; Sutisna, Sutisna (Technium Sustainability, 2024)
The fundamentals of sound foundation management can assist businesses in reducing the risks associated with performance management. Principles like accountability, transparency, responsibility, fairness, and justice are all part of the GCG in practice. Businesses can lower the risk of fraud and data manipulation by putting GCG principles into practice and ensuring that the decision- making process is conducted in an open, responsible, and fair manner. Establishing a code of ethics and strong foundation management standards, as well as boosting the openness of financial reports, are some GCG measures that can aid in reducing the risks associated with organisational performance management. However, organisations must also take into account other elements including effective risk management, the application of ethical standards, and the creation of a strong organisational culture in order to mitigate the risks associated with organisational performance management. Good corporate governance is not the only solution to this problem. In actuality, including GCG into a comprehensive risk management plan can assist businesses in improving performance and gaining the confidence of stakeholders. Therefore, in order to enhance performance and reduce risks associated with financial, ethical, and governance difficulties, businesses must pay attention to GCG techniques while mitigating organisational performance management risks.